COLLABORATION OF HEALTH SERVICES IN PREVENTION OF TUBERCULOSIS DISEASE IN INMATES AT CLASS IIA ABEPURA CORRECTIONS INSTITUTION - Itaar, Faldy Fernando; Santoso, Iman (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to analyze the collaboration of health services in preventing tuberculosis (TB) in Class IIA Abepura Prison. Qualitative methods are used to identify and evaluate health service practices based on the Levey Loomba framework, which includes promotive, preventive, curative, and rehabilitative services. The results of the study indicate that effective communication, respect, appropriate decision-making, and constructive feedback play an important role in the success of health service collaboration. However, there are obstacles in terms of health awareness of inmates and hygiene conditions that affect the effectiveness of TB prevention. Recommendations include increasing health socialization and improving sanitation conditions in prisons. This study is expected to provide insight into improving health services for inmates in correctional institutions. Keywords: Collaboration; Health Services; Tuberculosis